Kolaborasi Pentahelix dalam Pengelolaan Wisata Budaya pada Desa Wisata: Studi Kasus Desa Wisata Melinggih Kelod, Payangan - Santi Diwyarthi, Ni Desak Made; Pramana, I Dewa Putu Hendri; Adi Pratama, I Wayan; Mas Wiartha, Nyoman Gede; Jata, I Wayan (Jayapangus Press, 2025)
This research is a descriptive study with a qualitative approach conducted from March to April 2025. It explores the development of Melinggih Kelod Tourism Village in Payangan District, Gianyar Regency, through the Pentahelix approach involving government, academics, business actors, local communities, and media. The research methods include observation, document study, and interviews, utilizing both primary and secondary data sources. Data collection techniques employed purposive sampling, selecting participants who were deemed representative of the research population. Interviews were conducted with 20 individuals, including community leaders, the head of the tourism awareness group (Pokdarwis), members of the youth community (sekeha truna and truni), tourism entrepreneurs in Melinggih Kelod Tourism Village, academics from the Bali Tourism Polytechnic, and digital marketing experts. The data analysis technique includes data reduction, data display, and conclusion drawing and verification, based on the theory of Miles and Huberman. The research findings indicate that the implementation of this model contributes to an increase in tourist numbers, community involvement in the tourism sector, and village economic growth, particularly through community-based enterprises such as homestays, culinary ventures, and cultural attractions found in Melinggih Kelod Tourism Village, Payangan District, Gianyar Regency.Theoretical support from Collaborative Governance, Social Capital Theory, Diffusion of Innovation, and Sustainability Theory emphasizes that synergy among various stakeholders plays a role in strengthening the competitiveness and sustainability of the tourism village. Despite challenges such as limited infrastructure, the status of the village as an Independent Tourism Village demonstrates that community-based management, supported by innovation and sustainable empowerment, can enhance community welfare while preserving local culture.